(untitled) (GYMNASIUM, 2025)
This study investigates the effects of a 10-week CrossFit training program on the physical fitness of sambo athletes, focusing on strength, endurance, agility, and reaction speed. Twentyone athletes, aged 18-24, were divided into two groups: a control group continuing their traditional training and an experimental group completing CrossFit three times a week. Both groups underwent 8 performance tests assessing general and special fitness, strength, endurance, and agility, before and after the intervention. Statistically significant improvements (p < 0.05) were observed in three out of eight tests for the experimental group, specifically in abdominal strength (p<0.05), general fitness (p<0.02), and grip strength (p<0.04). While the experimental group showed positive trends, the overall impact was partial, with only three tests showing significant improvement. These results suggest that extending the training program to 6-8 months could lead to more substantial gains in physical performance.